PENGARUH CORPORATE GOVERNANCE DAN PENGUNGKAPAN ESG TERHADAP KINERJA PERUSAHAAN YANG TERINDEKS SCORE RISIKO ESG TINGGI - Arvi Lingga, Tasha Putri; Linda, Linda; Fuadi, Raida (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This research aims to examine the influence of corporate governance and Environmental, Social, and Governance (ESG) disclosure on company performace, as well as to investigate the differences in company performance before and after being indexed with high and severe ESG risk scores. The population in this study includes all companies with ESG risk scores. The data used is secondary data derived from annual and sustainability reports of companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The data was tested using SPSS 26 software. The findings of the study indicate that independent commissioners and the board of directors significantly influence company performance, while the audit committee and ESG disclosure do not show a significant impact. Additionally, the LQ 45 index as a dummy variable also has a considerable influence on company performance. There is no substantial difference in company performance before and after being indexed with high and severe ESG risk scores. The conclusion of this study confirms that corporate governance practices and ESG disclosure play an important role in achieving good company performance.